The Role Of Millennial Farmers in Supporting Agricultural Product Exports in Indonesia - Antonia Celia Vionita; Tia Mariani Supardi; Cakti Indra Gunawan (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2024)
This study aims to determine the increasing interest of the millennial generation in utilizing information and communication technology so that the distribution and marketing of agricultural products becomes more effective and efficient. The method used in this research uses descriptive, qualitative analysis with literature comparison. The results of the study show that the millennial generation has great potential as agents of change in the agricultural sector through the integration of digital technology and modern agricultural innovation. The government has also launched various programs, including the Millennial Farmer program, to increase the involvement of the younger generation in agriculture. Although there are still challenges such as low interest and negative image of the farming profession, the role of millennial farmers has proven significant in driving agricultural productivity and export competitiveness in the global market.